Effect of pruning intensities of three woody leguminous species grown in alley cropping with maize and cowpea on an alfisol - Duguma, B.; Kang, B.; Okali, D.U.U. (1988)
Field trials were carried out on an Oxic Paleustalf in the humid zone of southwestern Nigeria with Leucaena leucocephala (Lam.) de Wit,Gliricidia sepium (Jacq.) Steud. and Sesbania grandiflora (L.) Pers. alley cropped with maize and cowpea. The three leguminous woody species were grown in hedgerows spaced at 2 m. Trials were carried out one year after establishment of the hedgerows using a split-plot design with four replications. TheLeucaena trial had twenty pruning combinations consisting of five pruning heights (25, 50, 75, 100 and 150 cm) and four pruning frequencies (monthly, bi-, tri- and six-monthly). The Gliricidia andSesbania hedgerows were subjected to nine pruning intensities consisting of three pruning heights (25, 50 and 100 cm) and three pruning intensities (monthly, tri- and six-monthly). For the three woody species, biomass, dry wood and nitrogen yield from the hedgerow prunings increased with decreasing pruning frequency and increasing pruning height. Biomass, dry wood and nitrogen yields were in the following orderLeucaena >Gliricidia >Sesbania. The various pruning intensities had no effect on survival of Leucaena plants. Pruning frequency had a larger effect than pruning height on survival of Gliricidia and Sesbania plants. With monthly pruning, about 25 percent of the Gliricidia and all of the Sesbania plants died within six months of repeated pruning. Even with lower pruning frequency Sesbania plants showed lower survival rates than Gliricidia or Leucaena. The various pruning intensities of all the hedgerow species had more pronounced effects on the grain yield of the alley cropped cowpea than on maize grain yield. Higher maize and cowpea yields were obtained with increasing pruning frequency and decreasing pruning height.